Apocarotenoids: Sources, Classification and Their Potential Application as Food Additives - Indah Hartati; Vita Paramita (Research in Chemical Engineering, 2023)
Apocarotenoids are the degradation product of the enzymatic and or non enzymatic cleavage of carotenoids. Apocarotenoids are present in plants, fungi, bacteria and a certain animal species. There have been large numbers of apocaretonoids identified as the consequence of the great variety of naturally occurring carotenoids. Apocarotenoids can be found as volatile, semi-volatile or non-volatile compounds based on their chemical structures, while based on the number of the carbon atoms contained in their structure, apocarotenoids is classify into triporoids, cyclofarnesoids and methylhexanoids. Bibliometric analysis performed on publication having “apocarotenoids” keywords informs that crocin, pirocrocin, saffron and crocus sativus nodules appear in the overlay visualization. The appearance is attributed to the great potential application and commercialization of crocin which is originated from saffron. The bibliometric analysis also shows that there is food additive nodule appear which imply the strong correlation and potential application of apocarotenoids as food additive. The potential utilization and the commercial production of apocarotenoids are challenged by the the genetic diversity as well as the high cost, time consuming and seasonal production of natural apocarotenoids isolation process. Chemical synthesis, engineering biosynthesis and bio-manufacturing using microbes provide a promising and economical alternative.